2009
DOI: 10.1021/nl9012979
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Surface Charges of Individual Biomolecules

Abstract: Surface charges play a key role in determining the structure and function of proteins, DNA, and larger biomolecular structures. Here we report on the measurement of the electrostatic surface potential of individual DNA and avidin molecules with nanometer resolution using Kelvin probe force microscopy. We also show, for the first time, the surface potential of buffer salts shielding individual DNA molecules, which would not be possible with conventional ensemble techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 29 publications
5
95
0
Order By: Relevance
“…KPFM has been applied to measure the potentials of avidin and DNA at molecular level [34]; the negative potential of a single strand of DNA can be masked by the interaction with its complementary DNA strand [29]. Our results revealed that Φ s distribution histograms were altered by PS micelle incorporation and various ROS stimulations.…”
Section: Resultsmentioning
confidence: 86%
“…KPFM has been applied to measure the potentials of avidin and DNA at molecular level [34]; the negative potential of a single strand of DNA can be masked by the interaction with its complementary DNA strand [29]. Our results revealed that Φ s distribution histograms were altered by PS micelle incorporation and various ROS stimulations.…”
Section: Resultsmentioning
confidence: 86%
“…SKPM has been widely used to characterize biomolecular 10 , organic 11 and semiconductor 12,13 materials. The measured quantity, namely the electrical surface potential, may arise on the sample due to electrostatic charging or to chemical potential differences between inhomogeneous chemical phases.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al [36] reported a highly sensitive mutation detection with a gold nanoparticle (AuNP)-based platform (Figure 2d) by evaluating the surface potential change of each AuNP on silicon substrate, during probe DNA modification and target DNA hybridization, with a detection limit of 3.3 pM. Leung et al [37] showed the single-molecule detection of avidin molecules and DNA, with a resolution of five basic amino acids. They based the expected charge pattern measurements on individual DNA molecules and proteins after further refinements.…”
Section: Kelvin Probe Force Microscopy (Kfm)mentioning
confidence: 99%